1995
DOI: 10.1007/bf00192744
|View full text |Cite
|
Sign up to set email alerts
|

Effects of altitude (4300 M) on the pharmacokinetics of caffeine and cardio-green in humans

Abstract: The effects of chronic exposure to high altitude on the pharmacokinetics of caffeine and cardio-green (ICG) were examined in eight healthy males (23-35 y) at sea level (SEA) and following 16 days residence at 4300 m (ALT). ICG (0.5 mg. kg-1) was administered as an intravenous bolus and caffeine (4 mg. kg-1) in an orally ingested solution. The concentration of ICG, caffeine, and the primary metabolites of caffeine (MET) were determined in serial blood samples and their pharmacokinetics computed. In comparison t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 12 publications
1
10
0
Order By: Relevance
“…This study only tested the effect of hypoxia on the pharmacokinetics of caffeine after long-term (16 weeks) exposure to high altitude (4300 m). 13 In this study hypoxia caused an increase in caffeine clearance (117 versus 86 ml/min per kilogram) and a decrease in caffeine halflife (t 1/2 ) (4.7 versus 6.7 hours) in 8 healthy male subjects, implying an induction of CYP1A2.…”
Section: Resultsmentioning
confidence: 58%
See 1 more Smart Citation
“…This study only tested the effect of hypoxia on the pharmacokinetics of caffeine after long-term (16 weeks) exposure to high altitude (4300 m). 13 In this study hypoxia caused an increase in caffeine clearance (117 versus 86 ml/min per kilogram) and a decrease in caffeine halflife (t 1/2 ) (4.7 versus 6.7 hours) in 8 healthy male subjects, implying an induction of CYP1A2.…”
Section: Resultsmentioning
confidence: 58%
“…11,12 In contrast, caffeine clearance (also mainly CYP1A2 mediated) increased in healthy subjects after long-term exposure to altitude-induced hypoxemia. 13 Exposure to high altitude has for many years been used as an experimental model of adaptation to hypoxia. After such exposure, arterial PO 2 decreases significantly and several other biologic parameters conform to the general pattern of physiologic adaptation to hypoxia.…”
mentioning
confidence: 99%
“…They concluded that the increase in caffeine clearance was owing to increased hepatic blood flow. These same investigators (Kamimori et al, 1995b) then studied the issue in eight males after 16 days at 4300 m. Compared to sea level, the half-life of caffeine decreased from 6.7 to 4.7 h, the area under the curve (AUC) decreased by 32%, and clearance increased 36%. They also reported an increase in the AUC ratio of metabolites to caffeine, suggesting that either metabolite formation or elimination was increased at high altitude.…”
Section: Pharmacodynamics and Metabolism Of Caffeine At High Altitudementioning
confidence: 95%
“…A number of mechanisms could explain the relationship between suicide or depression and living at altitude (Haws et al, 2009), including the lower blood oxygen saturations that occur at higher altitudes (Katz, 1982;Hackett and Roach, 2012). Indeed, barometric pressure, drug pharmacokinetics, and metabolism-all of which change with altitude-may also affect human behavior, mental health, and suicide risk (Kamimori et al, 1995;Ritschel et al, 1996;Jurgens et al, 2002;Arancibia et al, 2003;Schory et al, 2003;Maldonado et al, 2009).…”
mentioning
confidence: 99%